Donor fund empowerment strategy in increasing donor trust: A case study on Lazismu Sidoarjo - Ilmi, Muhammad Nasrulloh; Maesaroh, Imas (Universitas Islam Indonesia, 2024)
IntroductionIndonesians are known for their philanthropic behavior, which can be seen from the number of zakat and infaq organizations in Indonesia.ObjectivesThis study aims to analyze the strategy of empowering donor funds and its effectiveness in increasing donor trust in Lazismu Sidoarjo.MethodData was collected using a qualitative approach through in-depth interviews with 14 informants, field observations, and document analysis.ResultsThe results showed that Lazismu Sidoarjo implemented a distribution strategy through 6 pillar programs (education, economy, social, environment, health, and da'wah) with an effectiveness rate of 85% based on the increase in the number of donors from 2021-2024. The effectiveness of the strategy is supported by three main activities: financial transparency, program publication, and activity documentation.ImplicationsThis study highlights the importance of transparent, accessible, and documented donor fund management to ensure trust. Zakat and infaq organizations can use the findings to improve public trust.Originality/NoveltyThis research contributes to developing a donor fund management model that can increase public trust in Amil Zakat institutions.